Radionuclides contamination of leaves of woody plants growing within the CHNPP cooling pond - V. K. Shynkarenko; S. A. Paskevych; Y. A. Menshenin; O. O. Odintsov (Ядерна фізика та енергетика)
The data on the state of radioactive contamination of leaves of plants growing directly on the territory of the drained part of the cooling pond of the Chernobyl NPP are presented. It was shown that the main source of contamination is the root intake of radionuclides (137Cs and 90Sr). This contamination is larger in previously drained areas compared to recently exposed ones. Hot particles were found on the leaf surface by autoradiography. Their total β-activity is a few percent of the total pollution. Possible sources of hot particles – resuspension in the air in the region of the northern part of the cooling pond are discussed.